On small fatigue crack growth rates in AA7085-T7452. (March 2022) - Main, Ben; Jones, Michael; Dixon, Ben; Barter, Simon
Highlights: Develops two new small-crack/near-threshold fatigue crack growth rate data sets for aluminium alloy 7085-T7452 using different experimental techniques. Develops a short fatigue crack growth rate model for 7085-T7452 from the preferred fractography data set and demonstrates its validity and improvement over available long crack data via blind prediction of an independent spectrum loaded coupon data set. Abstract: Aluminium alloy 7085-T7452 is a material developed by Alcoa (now Arconic) for its favourable mechanical properties in thick, forged aluminium aerospace structural parts. Currently reported fatigue crack growth rate data for 7085-T7452 in the open literature does not fully characterise the small crack growth behaviour of this material. The growth rates of small fatigue cracks are important since they often govern the useful service life of large primary structural parts in the aerospace industry. In this paper, small fatigue crack growth rates were measured experimentally using two methods and compared with data available in the open literature for longer cracks. The fractography based method was found to develop fatigue crack growth data that better characterised the small crack regime and so these results were then developed into a fatigue crack growth model which was evaluated for its ability to predict an independent set of 7085-T7452 specimens tested with a complex aircraft wing bending plus buffet loading spectrum. The fractography method based small crack growth rate model was able to robustly predict fatigue crack growth under this complex variable amplitude sequence from small, realistic initial discontinuity sizes better than long crack data, yet it is not without need of further refinement.